2012
DOI: 10.3855/jidc.1967
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical presentation, and patterns of drug resistance of Salmonella Typhi in Karachi, Pakistan

Abstract: Introduction: Enteric fever remains a major public health problem in Asia. Planning appropriate preventive measures such as immunization requires a clear understanding of disease burden. We conducted a community-based surveillance for Salmonella Typhi infection in children in Karachi, Pakistan. Methodology: A de jure household census was conducted at baseline in the study setting to enumerate all individuals. A health-care facilitybased passive surveillance system was used to capture episodes of fever lasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 20 publications
6
30
1
1
Order By: Relevance
“…The incidence estimates reported from pediatric population-based studies (51–76 cases/100,000 person-years) did not differ substantially from incidence reported in adults and children from South Asian countries [23], [24]. In all pediatric studies, S. Paratyphi A accounted for a lower proportion of enteric fever cases (8.6–17.0%) than in studies which included adults, with the exception of one study conducted in New Delhi, India [23][27].…”
Section: Resultsmentioning
confidence: 56%
“…The incidence estimates reported from pediatric population-based studies (51–76 cases/100,000 person-years) did not differ substantially from incidence reported in adults and children from South Asian countries [23], [24]. In all pediatric studies, S. Paratyphi A accounted for a lower proportion of enteric fever cases (8.6–17.0%) than in studies which included adults, with the exception of one study conducted in New Delhi, India [23][27].…”
Section: Resultsmentioning
confidence: 56%
“…investigated 293 isolates associated with travel, particularly to Southeast Asia and Mexico, and observed that 17% were MDRST and 7% were NARST . A similar trend of combined resistance to first‐line drugs and relatively higher resistance to nalidixic acid or DCS (MIC = 0.12–1 μg/mL; full‐resistance is ≥2 μg/mL) was observed in India, in a retrospective study of isolates from Pakistan and Bangladesh, and in two studies investigating isolates from children in Pakistan and in Cambodia . Other recent studies have demonstrated a trend of higher percentages of isolates showing nalidixic acid resistance compared to MDR from the first‐line drugs.…”
Section: Nalidixic Acid–resistant S Typhi and Its Clonal Emergencementioning
confidence: 53%
“…However, fl uoroquinolone resistance is increasing in India (44%) and Pakistan (58%), and susceptibility is decreasing in Congo (15%) and Cambodia (80%). [263][264][265][266] In Kenya, 267 more than 77% of the S typhi were multidrug resistant, much higher than the reported 52% in Ghana 268 and 29% in Egypt. 263 Additionally, the proportion of S typhi in Kenya that are multidrug resistant and resistant to nalidixic acid with decreased susceptibility to fl uoroquinolones had risen from 1% in 2000 to nearly 25% in 2008.…”
Section: Diarrhoeal Pathogensmentioning
confidence: 91%